Avaliação de desempenho do modelo fotoquímico CMAQ utilizando diferentes condições de contorno em uma região urbana e industrializada - Pedruzzi, Rizzieri (2016)
The purpose of this study was to evaluate the influence of the boundary conditions (BCON) in the CMAQ model simulations over the Metropolitan Region of Grande Vitória (RMGV) for MP10 and O3 pollution. It was made four scenarios of August 2010 with different boundary conditions. The first scenario (M1) using fixed, time-independent boundary conditions with zero concentration (zero) for all pollutants; a second scenario (M2) with fixed, timeindependent concentration values, with average values from monitoring stations from RMGV and from Aracruz’s stations on north and Anchieta’s stations on south; the third scenario (M3) used boundary conditions varying with time from a previous simulation with CMAQ over a larger area, centered on RMGV; and finally, the fourth scenario (M4) usin g boundary conditions varying with time from simulations of global model GEOS-Chem. All scenarios used the same meteorology conditions and pollutant emissions, meteorological conditions was generated by the model WRF version 3.6.1 and pollutant emissions inventory are from the official emissions inventory of RMGV. The air quality simulations were made with a domain 61 x 79 km centered on coordinates -20,25ºS, -40,28ºW with a resolution of 1 km, using the CB05 and Aero6 and still analyzer CMAQ processes (PROCAN). The results were compared with the measured data in monitoring stations from RMGV. The results showed that for PM10, the boundary conditions were not so influential on the simulated concentrations, with small variations of concentrations between the tests, but, in general, M3 and M4 methods achieved the best results for statistics, however, the M2 method is not totally wrong but should be cautious in using this method. It was observed different behaviors between monitoring stations, where there are some that have been overestimated values in a few hours and others with understated concentrations, occurred probably because the grid size associated with weather conditions and temporal variation of emissions. For ozone, it was noted that the boundary conditions had a large influence on modeled concentrations, and may also influence the increased of production of O3 not only by chemical reactions, but also by advection processes and atmospheric diffusion. It was observed on scenario M1 that the O3 modeled concentrations were very small and do not represent reality. On M2 and M3 scenarios, concentrations were overestimated, on monitoring stations and in areas near the boundaries of the domain, mainly in the western portion. The M4 scenario achieved the best results of concentrations and statistics, which is the most advisable when the goal is to evaluate the ozone. As the high resolution domain applied to CMAQ had only 61x79km was noted that the boundary conditions affect directly across the grid field, especially for ozone, by using the process analysis preprocessor (PROCAN). When the boundary concentrations are high, regardless of being fixed or varying with time, the advection processes and turbulent diffusion adds a large amount of mass in domain's borders, overestimating the modeled concentrations.